Histoprotective Effect of Salmonella typhimurium non-Porin Outer Membrane Proteins Against Salmonellosis in Mice - Abdulrasool, Mohammed Ridha; Salih, Shahlaa M; Al-Shaibani, Abdulwahid B (Al-Nahrain Journal of Science, 2018)
This study was designed to evaluate the histoprotective effect of non-porin outer membrane proteins against Salmonella infection in mice. S. typhimurium was isolated from stool of infants suffering from diahrria after performing microscopic examination, some biochemical tests and API 20E identification. The outer membrane proteins (OMPs) of S. typhimurium was extracted and analyzed by Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE). Results of protein profile of the S. typhimurium outer membrane proteins revealed that bands with molecular weight ranged between 33-203 kDa were present. Purification by ion exchange chromatography on DEAE- cellulose was carried out. Results of the purified OMPs by (SDS-PAGE) exhibited that two bands with molecular weights of 33 and 203 KDa were present, then mice treated with non-porin OMPs and infected with S. typhimurium. Histopathological study exhibited that infection of mice with S. typhimurium showed shortening of intestinal villi with inflammatory cells infiltrate inside the villi and multiple necrosis in the spleen and liver. While mice treated with non-porin OMPs and infected with S. typhimurium showed looking like normal appearance of intestinal villi and normal structure appearance of spleen and liver.